Better or Worse? The Independent Prognostic Role of HPV-16 or HPV-18 Positivity in Patients With Cervical Cancer: A Meta-Analysis and Systematic Review - Chen, Xing; Zhang, Ping; Chen, Shanshan; Zhu, Hanxiao; Wang, Kai; Ye, Liya; Wang, Jun; Yu, Junhui; Mei, Shuangshuang; Wang, Zhengrong; Cheng, Xiaodong (Frontiers in Oncology, 2020)
Background: The literature reports conflicting results regarding the effect of human papillomavirus (HPV) genotype 16 (HPV-16)/18 (HPV-18) positivity on cervical cancer (CC) prognosis. Aim: To conduct a meta-analysis to examine the effect of HPV-16/18 positivity on the prognosis of patients with CC. Methods: PubMed, Embase, and the Cochrane Library were searched for available papers published up to March 2020. The main outcome was the hazard ratio (HR) of overall survival (OS) or disease-free survival (DFS) comparing HPV-16 or HPV-18 positivity and negativity. The random-effects model was used for synthesizing survival outcomes. Results: Nine studies and 2,028 patients were included. Four studies reported OS in HPV-16 positivity, and no association was found between HPV-16 positivity and OS to CC (HR = 0.79, 95% CI: 0.26–2.39, P = 0.675). Three studies reported DFS in HPV-16 positivity, and no association was found between HPV-16 positivity and DFS to CC (HR = 0.80, 95% CI: 0.30–2.11, P = 0.654). Two studies reported DFS in HPV-18 positivity, and no association was found between HPV-18 positivity and DFS to CC (HR = 0.99, 95% CI: 0.55–1.78, P = 0.984). One study reported progression-free survival (PFS) in HPV-18 positivity, and an association was observed between HPV-18 positivity and PFS to CC (HR = 2.66, 95% CI: 1.44–4.94, P = 0.002). The sensitivity analyses showed that one study biased the analysis of the association between HPV-16 and OS, and another study biased the association between HPV-16 and DFS. Conclusion: The presence of HPV-16 and HPV-18 positivity appears to have no significant association with prognosis in CC in either OS or PFS. The presence of HPV-16 or HPV-18 positivity has no significant association with prognosis in CC in either OS or PFS.